Multi-Factorial Management of Fall Risk in the Home Setting With Use of Innovative Technology: A Case Study (International Journal of Studies in Nursing, 2020)
Fall risk and fall injury risk are a raising concern for older adults living in the home and community environment. Injuries from falls account for reduced independence for older adults in the form of limitations of activities of daily living performance and significant dependency for ambulation. Up to 50% of those who suffer a hip fracture from a fall will not be able to return to their prior level of living. Serious fall injuries create a necessity to move into a setting where increased levels of care are provided. The ability to remain in the most desired setting of their own home is a critical part of successfully aging in place. According to the Centers of Disease Control, 36 million older adults in the United States suffered a fall in 2018 with 8 million reported injuries. With the expansion of the older adult population, these numbers are anticipated to inflate up to 52 million falls with 12 million reported fall injuries by the year 2030. Several countries have adopted fall risk mitigation programs for fall risk identification in primary care and community provision of fall management strategies. Traditional methods of fall risk management follow the American Geriatrics Society’s and British Geriatrics Society’s Clinical Practice Guideline. Though great strides are taken to intervene on the modifiable risk factors for falls, the risk of falls for many individuals remains. Introduction of new and innovative technologies can offer increased safety and ability to participate in functional mobility for those most at risk of falls and fall injuries.